Use of Postexposure Prophylaxis After Occupational Exposure to Zaire ebolavirus - Wong, Karen K. (Clin Infect Dis, 2016)
From September 2014 to April 2015, 6 persons who had occupational exposures to Zaire ebolavirus in West Africa received investigational agent rVSV-ZEBOV or TKM-100802 for postexposure prophylaxis and were monitored in the United States. All patients experienced self-limited symptoms after postexposure prophylaxis; none developed Ebola virus disease.